(untitled) - Garsten, Christina (New York, 2004)
This book looks at the powerful global discourse on employability in labor markets, by providing case studies of local work practices. This is key to understanding contemporary changes in the workings of labor markets and highlights changes in ideas regarding responsibility and learning. This is the first major study of the connection between the global discourse and local practices of employability and provides a valuable contribution to the workings of labor markets today.
Keywords: Occupational training,Occupational retraining,Continuing education,Work ethic; European Union countries,European Union countrie,European Union countries,European Union countries